1994
DOI: 10.1142/s0217979294001639
|View full text |Cite
|
Sign up to set email alerts
|

Non-Equilibrium Coherent Vortex States and Subharmonic Giant Shapiro Steps in Josephson Junction Arrays

Abstract: This is a review of recent work on the dynamic response of Josephson junction arrays driven by dc and ac currents. The arrays are modeled by the resistively shunted Josephson junction model, appropriate for proximity effect junctions, including self-induced magnetic fields as well as disorder. The relevance of the self-induced fields is measured as a function of a parameter κ = λ L /a, with λ L the London penetration depth of the arrays, and a the lattice spacing. The transition from Type II (κ > 1) to Type I … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…This behavior is consistent with the assumption that phase locking in two-dimensional arrays of Josephson junctions is described by coherent vortex motion perpendicular to the transport current. [3][4][5][6][7][8][9][10][11][12][13] In some cases, we observed that all junctions of one row, but not the edge junctions, give a voltage signal. The inhomogeneous distribution of dc and ac currents in the array, due to current-induced magnetic fields, 11 may be responsible for this phenomenon.…”
Section: B Distribution Of Phase-locked Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is consistent with the assumption that phase locking in two-dimensional arrays of Josephson junctions is described by coherent vortex motion perpendicular to the transport current. [3][4][5][6][7][8][9][10][11][12][13] In some cases, we observed that all junctions of one row, but not the edge junctions, give a voltage signal. The inhomogeneous distribution of dc and ac currents in the array, due to current-induced magnetic fields, 11 may be responsible for this phenomenon.…”
Section: B Distribution Of Phase-locked Junctionsmentioning
confidence: 99%
“…Results on the amplitude ⌬I n of a particular Shapiro step of order n versus the applied rf power are obtained experimentally [4][5][6] or by numerical simulations. 7-10, 12 Phillips et al observed in numerical simulations a finite slope of Shapiro steps due to bias current nonuniformity because of the self-induced magnetic field of the bias current. 11 Hagenaars numerically found Shapiro steps showing finite slope due to nonperfect phase locking of all the junctions due to the motion of vortices that do not participate in the coherent motion.…”
Section: Introductionmentioning
confidence: 99%
“…2 Apart from the applications, two-dimensional arrays have been also investigated as an interesting nonlinear system both experimentally and theoretically. 3,4 In the study of such arrays two classes of models have been proposed to describe the dynamics: ͑1͒ Models that neglect the self-field effects. These model are often called ''uniformly frustrated XY ,'' 5-7 because the Hamiltonian for this model is similar to that of a square flat lattice of spins in the magnetic field ͑for that reason it is also called the spin-glass model͒.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Domìnguez and Josè have reviewed the topic in Ref. 4. In spite of the simplicity of model ͑1͒, it has been able to explain most of the experimental observations on twodimensional arrays, for example, giant Shapiro steps.…”
Section: Introductionmentioning
confidence: 99%
“…At low temperatures, intergranular flux penetration is dominant and the magnetic properties of this class of superconductors can be well described by Josephsonjunction array models. [1][2][3][4][5][6][7][8][9] In some of these models 2,7 the presence of the physical grains is taken into account by means of the inductive couplings between junctions and flux penetration after zero-field cooling ͑ZFC͒ takes place exclusively in the intergranular regions because of 2 variations of the gauge-invariant superconducting phase difference of the junctions. 10 However, in order to account for the complete response of the system at higher fields or temperatures, or for different sample histories, intragranular flux penetration must be allowed.…”
Section: Introductionmentioning
confidence: 99%